Consequences of cyberaggression on Social Network on mental health of Italian adults. (20th October 2021) - Martella, M; Bert, F; Colli, G; Lo Moro, G; Pagani, A; Tatti, R; Scaioli, G; Siliquini, R
Abstract: Background: Cyberaggression (CyA) comprehends a broad spectrum of hostile behaviours carried out through electronic means. Acts of CyA were studied mostly among adolescents. This cross-sectional study aims to evaluate the nature, extent and outcomes in terms of depressive and anxiety symptoms as well psychosomatic disorders in adults in Italy. Methods: An internet-based survey comprehensive of 34 items was distributed through Social Media and targeted only adults. Descriptive analysis and correlation tests were performed in order to identify the extent of the CyA phenomenon. Results: The survey received a response from 341 Participants (60% women), 43% of them declared to have been victim of CyA almost 1 time in their life and the most representative forms were insults (24.7%) and harassment (19.9%). Only 13% of participants were author of acts of CyA almost 1 time in their life, and 11% of them insulted someone else online. The 74.1% was bystander of CyA episodes as insults (62.7%), discrimination (62%) and defamation (47.8%). According to 95.1% of participants, these episodes were seen on Social Network, 17% on Facebook. The 39.5% of participants asserted an increased frequency of the events during the pandemic restriction. The main reasons of CyA declared were politics (70%), racism (65.8%), sexual orientation (65%) and female gender (53.1%). Chi square Test showed a significant correlation only between sexual orientation and victimization (69.4% of non-heterosexual asserted to be victim). The 33.6% of victims of CyA asserted anxiety and sadness after episodes, while the 39.8% stated to be angry. Conclusions: CyA episodes are widespread in the European context and potentially harmful for mental health of victims. Sexual and ethnic minorities and females are more frequently the target. Pandemics enhanced this phenomenon. European public health professionals should take into careful consideration this issue for its potential negative consequences. Key messages: Cyberaggression is a widespread phenomenon in Europe with potential negative consequences on mental health of victims, especially during the current pandemic. Sexual and ethnic minorities and females are more frequently the target of cyberbullying and European public health professionals and policy-makers should implement strategies to prevent this issue.